What Distinguishes Suicide Attempters From Suicide Ideators? A Meta‐Analysis of Potential Factors. (11th February 2016) - May, Alexis M.; Klonsky, E. David
Abstract : Most suicide ideators do not attempt suicide. Thus, it is useful to understand what differentiates attempters from ideators. We meta‐analyzed 27 studies comparing sociodemographic and clinical variables between attempters and ideators. When comparing ideators to nonsuicidal individuals, there were several large effects. For example, depression and PTSD were markedly elevated among ideators ( d =  .85–.90). In contrast, when comparing attempters to ideators, all 12 variables had negligible to moderate effects. Specifically, depression, alcohol use disorders, hopelessness, gender, race, marital status, and education all were similar in attempters and ideators ( d  =   −.05 to .31). Anxiety disorders, PTSD, drug use disorders, and sexual abuse history were moderately elevated in attempters compared to ideators ( d =  .48–.52). Implications for theory and practice are discussed.